Equidade de gênero no âmbito corporativo sob a ótica do executivo - Melo, Elaine Leão Inácio de (2012)
This work aims at to map out the profile of executive men, their careers in the work market and their perception concerning the differences between male and female characteristics in both the corporate world and their personal lives. The collection of such perceptions has been gathered through semi-open structured interviews with directors and some managers of various enterprises. The interviews covered all the individual’s career, academic background and professional experience up to the time he took up an executive position. The questions covered daily activities, personal or genre traits that make the tasks easier and help climbing up in the career and ends with aspects of the personal life always including questions on genre. Based on bibliographies and statements in the interviews, and taking into account the diversity of cultures, beliefs coupled with the existing psychological, social, genre and sexual identities plurality nowadays, the conclusion is that it is really impossible to conceive hegemony in relation to identities as they are not steady, immutable. At each decade, we realize that culture, life styles and behaviors are constantly changing to fit the needs of the moment.